Optoelectronic system for detecting short-circuits in low voltage networks - Barczak, Kamil; Juraszek, Janusz (Photonics Letters of Poland, 2022)
The paper presents the concept of using a fiber-optic current sensor with external conversion (OFCS-EC) in a power system. The sensor was developed in the Department of Optoelectronics and was tested in a laboratory. The focus was on the use of OFCS-EC in a real low voltage network. The main purpose of the presented measurement system will be to record network disturbance states with high accuracy. The experiment is to answer the question whether the recorded current waveforms in fault states and the measurement transmission speed will be useful enough to be able to predict, identify and, consequently, prevent losses and damage to devices caused by disturbances in low voltage networks. Full Text: PDF References S. Ziegler, R.C. Woodward, H.H.C. Iu, L.J. Borle, "Current Sensing Techniques: A Review", IEEE Sens. J. 9, 354 (2009). CrossRef R.M. Silva, H. Martins, I. Nascimento, J.M. Baptista, A.L. Ribeiro, J.L. Santos, P. Jorge, O. Frazão, "Optical Current Sensors for High Power Systems: A Review", Appl. Sci. 2, 602 (2012). CrossRef K. Barczak, K. Mazniewski, "Optical fiber current sensor with external conversion for measurements of low AC electric currents", Proc. SPIE, 10455 (2017). CrossRef K. Barczak, T. Pustelny, D. Dorosz, J. Dorosz, "Polarization maintaining fibers for application in magnetic field measurements", Eur. Phys. J.: Spec Top. 154, 11 (2008). CrossRef K. Barczak, T. Pustelny, D. Dorosz, J. Dorosz, "New Optical Glasses with High Refractive Indices for Applications in Optical Current Sensors", Acta Phys. Pol. A, 116, 247 (2009). CrossRef K. Barczak, "Optical fiber current sensor with external conversion", Proc. SPIE, 10034 (2016). CrossRef K. Barczak, D. Duda, K. Mazniewski, "Optical fiber current sensor with external conversion in high voltage environment", Proc. SPIE, 10830 (2018). CrossRef